(untitled) (Revista científica Olimpia, 2019)
The update of boys and girls in sports is one of the tasks of Physical Education, in which the games occupy a prominent place, recognized for their high educational value and in the development of children and youth, hence The objective of this article is based on the Preliminary study for the teaching of baseball 5, in the province of Sancti Spíritus. To this end, a characterization of the problematic situation in the spirit school environment was carried out and it was assessed , various trends on the problem The research was carried out with a significant sample of teachers and methodologists from the municipalities of the province of Sancti Spíritus that includes all levels of education, up to the upper average, without exception of schools with educational needs This new inclusive sport is a way to promote sports initiation from the Physical Education class and the sports program for everyone.